The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18410/jebmh/2019/188
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Unmet Need of Contraception Among Hiv Seropositive Women Attending Antiretroviral Treatment (Art) Clinic in Tertiary Care Centre

Abstract: BACKGROUND Contraceptive use among HIV positive women plays a crucial role in meeting their reproductive health needs. This is a study with the primary aim to estimate the magnitude of unmet need for family planning among HIV seropositive women of reproductive age in central India and to identify the various socio-demographic factors and reasons associated with unmet need for family planning. MATERIALS AND METHODS The study is an institutional cross-sectional study. The unmet need of 400 women with HIV positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
5
1
0
Order By: Relevance
“…Place of residence, educational status of the respondent, knowledge about FP, attitude toward FP, client satisfaction with FP service, women decision making power, and FP counseling service in ART clinics were the independent predictors of unmet need for FP among married women attending ART clinics. This research found that unmet need for FP (33%) to be consistent with the previous study in Addis Ababa, where the unmet need for FP among HIV-positive women was 31.1% [27], and in India, where 28.% of ART attending women had an unmet need for FP [8]. However, the result in this study is higher than the study in Ethiopia, as was the study in Hawassa (19.1%) [15] and Addis Ababa (25.1%) [14].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Place of residence, educational status of the respondent, knowledge about FP, attitude toward FP, client satisfaction with FP service, women decision making power, and FP counseling service in ART clinics were the independent predictors of unmet need for FP among married women attending ART clinics. This research found that unmet need for FP (33%) to be consistent with the previous study in Addis Ababa, where the unmet need for FP among HIV-positive women was 31.1% [27], and in India, where 28.% of ART attending women had an unmet need for FP [8]. However, the result in this study is higher than the study in Ethiopia, as was the study in Hawassa (19.1%) [15] and Addis Ababa (25.1%) [14].…”
Section: Discussionsupporting
confidence: 89%
“…Women live in a rural area was significantly associated with unmet need for FP. This result in line with other studies in Tigray [29], Nigeria [30], and India [8]. The possible explanation might be even if FP knowledge was even distributed in all residential areas, women living in rural areas were less exposed to messaging regarding FP [31].…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our findings, studies in Tigray [ 36 ] and Dire Dawa [ 38 ] in Ethiopia, Nigeria [ 34 ] and India [ 41 ] found that women living with HIV residing in rural areas were more likely to have unmet need for family planning than their counterparts from the urban areas. The probable explanation for this phenomenon is that women in rural areas have lower exposure to information and limited access to sexual and reproductive health services than their urban counterparts, as reported in surveys in Zambia and elsewhere [ 30 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Evidently, similar to our findings, studies in Tigray (32) and Dire Dawa (33) in Ethiopia, Nigeria and India (35) found that women living with HIV residing in rural areas were more likely to have unmet need for family planning than their counterparts from the urban areas. The probable explanation for this phenomenon is that women in rural areas have lower exposure to information and limited access to sexual and reproductive health services than their urban counterparts, as reported in surveys in Zambia and elsewhere (30, 31).…”
Section: Discussionsupporting
confidence: 91%